Prawda ekonomiczna według Jana Pawła II - Knabit OSB, o. Leon Stefan (Annales. Etyka w Życiu Gospodarczym, 2009)
It is important to specify terms – the truth is conformity of a word to a thing or an event, whereas a lie is making the truth unavailable to someone who has the right to it.John Paul II promoted the essential truth that a man is God’s creation; God knows what is good for his creation; human person is God’s image, then should act in such a manner that the image is clear. Faith has moral dimension-it is moral dimension. It is the source of practical involvement which remains in harmony with faith. The principles of one’s conduct are God’s commandments, whereas individualistic ethics, practised in the spirit of illusory freedom, prevents us from discovering the only certain truth-God.Contemporary crisis of society is that faith is rejected and as a result there is breaking off the essential and constitutive bond between the truth and freedom.In economy we can see that the truth in one’s conduct cannot withstand the style of the present geared towards profit. It is proper that the Church supports profit but the profit cannot be the only regulator of a company’s life. There are still human and moral factors. Economic growth should respect human values.Freedom in the economic and social area cannot be torn out from the truth about a human being.The meeting of the Church and the workers’ movement in 1980 showed that it is possible to demand ethics in economy in the name of the truth of a human being-then the civilisation of love is created with its main principles: a person before a thing, more important to be than to have, ethics before technology, mercy before justice, defeat evil with good.Problems existing in this area cannot be disregarded. The matter is important and urging – otherwise, as Pope Leo XIII said in the Encyclical Rerum Novarum, delaying would make evil incurable.